Refleksi Kristologis dalam Konteks Asia - Artha Yualin; Aprilia Pasca; Verra Verra; Sarmauli Sarmauli (CV. Rumoh Aceh Publishing, 2026)
This research aims to reflect on Christology in an Asian context. This research is beneficial for the development of theological science, particularly in the fields of Christology and contextual theology. This research uses a descriptive approach with a library research method. This study on Christological reflection in an Asian context focuses on the exploration, study, and analysis of various relevant written sources, both classical and contemporary. It can be concluded that Christology is the teaching about the person and work of Jesus Christ, which is inseparable from the doctrine of the Trinity and salvation. Christological reflection in an Asian context arises from the need to present the meaning of Jesus Christ in the reality of religious pluralism, poverty, and suffering that characterize Asian societies. Figures such as Kosuke Koyama with his Water Buffalo Theology emphasize simplicity and closeness to the common people; C.S. Song with his Story Theology emphasizes the importance of folklore and Asian cultural identity; and J.B. Banawiratma with his contextual approach opens dialogue with Islam. The application of contextual Christology in Asia is manifested in interfaith dialogue, social engagement to alleviate poverty, and contextual and tolerant Christian religious education.